Pengaruh internalisasi etika digital islami terhadap pembentukan akhlak siswa MTs S balimbing - Siska Andeska Putri; Sel Pitriyani; Gustina; Syahrur Ramli; Niatul Sovia; Rahmatul Riza (Institut Agama Islam Negeri Pontianak, 2026)
This study aims to analyze the influence of Islamic digital ethics internalization on the moral formation of students at Balimbing Private Islamic Junior High School. The specific problem is the gap between students' high religious understanding (88.6–95.5%) and problematic digital behavior, such as online bullying and digital dating practices. The expected solution is strengthening internalization of honesty, responsibility, tabayyu, and ḥayā values in digital technology use as a foundation for noble character formation. The hypothesis states there is a significant positive influence of Islamic digital ethics internalization on students' moral formation, arguing that internalized Islamic values become a moral filter in digital activities while shaping character in real life. The research employed a descriptive quantitative approach with Likert-scale questionnaires distributed to 60 student respondents at students at Balimbing Private Islamic Junior High School. Data analysis used SPSS through prerequisite tests (normality, homogeneity, linearity) and hypothesis testing with simple linear regression. Results showed data were normally distributed (Sig. > 0.05), homogeneous (Sig. 0.129), and had a linear relationship (Sig. deviation from linearity 0.765). Hypothesis testing proved a significant influence with the correlation coefficient (R) of 0.654 (strong category) and a determination coefficient (R²) of 0.145, meaning Islamic digital ethics internalization contributes 42.8% to students' moral formation. The regression equation Y = 12.432 + 0.587X indicates that each one-unit increase in Islamic digital ethics internalization increases moral formation by 0.587 units. The discussion reveals that internalizing ḥayā' values as an internal filter and strengthening moral feeling are key to bridging the gap between students' religious knowledge and digital behavior.